Arbitrase Alternatif Penyelesaian Sengketa Dalam Dunia Usaha (Investasi) Di Indonesia Dalam Persepektif Hukum Islam - Maásah, Zahrotul (BULLET : Jurnal Multidisiplin Ilmu, 2023)
It has become imperative for Indonesia to provide a platform for entrepreneurs to offer alternative options for resolving disputes in the business world because the business world has expanded limitlessly, supported by the rapid advancement of technology. This expansion has permeated every dimension of life and economic behavior, both legally and sociologically. With technological support, the ease of transactions is experienced by all parties. Nevertheless, this does not negate the possibility of conflicts arising between parties who have entered into business agreements. Therefore, the choice of resolving issues that are fast, cost-effective, confidential (impacting the credibility of the case), managed by those truly proficient in the field, and culminating in a final and binding decision, becomes crucial.There are several dispute resolution options in the business world, each with its own strengths and weaknesses. However, those involved in disputes have the choice to facilitate the resolution of their issues, making arbitration the appropriate choice for settling disputes in the business world. The question arises: why opt for arbitration?In arbitration, there are specifications; the process is confidential and closed, offering flexibility while operating within the existing legal framework. Arbiters have studied the applications and responses submitted by the parties involved. Furthermore, the parties involved are still able to maintain a good working relationship. They can choose the type of law to be applied and have the freedom to appoint an arbiter. Despite existing weaknesses, efforts are made to minimize the impact of unresolved disputes. In Islam, the majority religion in Indonesia, arbitration is permissible for conflict resolution.